The effects of heavy metal ions on the growth of Rhizopus arrhizus - Uslu, G; Özer, A; Ekiz, HI (Inst Lebensmitteltechnologie Analytische Chemie, 2002)
In this study, the effect of heavy metal ions on the biomass increase of Rhizopus arrhizus was investigated as a function of pH, temperature, metal ion concentration and initial sucrose concentration. The optimum pH values were found as 5.0, 3.5, 4.0, 4.5 and optimum temperatures as 30, 30, 25, 30 degreesC for control, cadmium(II), lead(II) and copper(II) ions, respectively. The biomass concentration increased with increasing initial sucrose concentration up to 30 mg L-1 and decreased with increasing metal ion concentration. The adsorbed cadmium(II), lead(II) and copper(II) amounts at the end of growth period of R. arrhizus were found as 8.7, 14.4 and 11.2 mg g cell(-1), respectively, for 50 mg L-1 initial metal ion concentration.
Keywords: biosorption; heavy metal ions; Rhizopus arrhizus; cell growth